The prognostic value of frailty in major trauma in older people - Alqarni, Abdullah (2024)
Background: The incidence of major trauma in older people is rising. Frailty significantly raises the probability of poor trauma outcomes in older people. The purpose of this thesis is to investigate the predictive value of frailty in major trauma as well as to determine the need for developing a frailty evaluation instrument specifically for older individuals who have had major trauma.